Selection of radio astronomical observation sites and its dependence on human generated RFI - Umar, Roslan; Abidin, Zamri Zainal; Ibrahim, Zainol Abidin; Rosli, Zulfazli; Noorazlan, Noorkhallaf (Research in astronomy and astrophysics, 2014)
We investigate the influence of population density on radio-frequency inter- ference （RFI） affecting radio astronomy. We use a new method to quantify the thresh- old of population density in order to determine the most suitable lower limit for site selection of a radio quiet zone （RQZ）. We found that there is a certain trend in the population density-RFI graph that increases rapidly at lower values and slows down to almost fiat at higher values. We use this trend to identify the thresholds for pop- ulation density that produce RFI. Using this method we found that, for frequencies up to 2.8 GHz, low, medium and high population densities affecting radio astronomy are below 150 ppl km-2, between i50 ppl km-2 and 5125 ppl km-~, and above 5125 ppl km-2 respectively. We also investigate the effect of population density on the environment of RFI in three astronomical windows, namely the deuterium, hydro- gen and hydroxyl lines. We find that a polynomial fitting to the population density produces a similar trend, giving similar thresholds for the effect of population density. We then compare our interference values to the standard threshold levels used by the International Telecommunication Union within these astronomical windows.